Analisis Sentimen Publik terkait Migrasi Tenaga Kerja Indonesia di Platform X menggunakan SVM-IndoBERT - Ata Amrullah (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2025)
Diverse public opinions on social and economic issues related to labor migration are often expressed on the social media platform X (Twitter). This research aims to classify public sentiment toward this phenomenon by analyzing tweets containing the hashtag KaburAjaDulu